ANALISIS YURIDIS ATAS PRINSIP PENDAFTARAN DESAIN INDUSTRI DI INDONESIA (STUDI PUTUSAN PENGADILAN NIAGA JAKARTA PUSAT NOMOR 49/DESAIN INDUSTRI/2004/PN/NIAGA.JKT.PST, SENGKETA KEMASAN/WADAH LULUR MANDI PURBA SARI) - DEWI NASUTION (PREMISE LAW JURNAL, 2016)
System of industrial design registration in Indonesia adopts a constitutive, who got / obtained the certificate of industrial design from the Ministry of Law and Human Rights are the holder of Design Indutri, although the provisions of Article 2 of Law No. 31 of 2000 on Industrial Designs entails the principle of novelty (novelty). The principle of novelty in the Law on Industrial Designs set with a first application filed and at the time of registration was filed, no other party can prove that such registration is not new or existing disclosure/ publication, whether written or unwritten. Consideration of the legal panel of judges in the Central Jakarta Commercial Court decision number 49/Industrial Design/2004/PN/Niaga.Jkt.Pst is already appropriate, given Shower Scrub registration bangkoang Sari has been qualified novelty (novelty), the Plaintiff is the first registrant who apply Packaging Industrial Design registration Sari bangkoang Shower Scrub. Legal protection of the owner of industrial design in Indonesia in principle include the protection of registered designs. Keywords: Legal Protection, Industrial Design Rights, Principle of Novelty